EFFECTIVE INVESTIGATIVE INTERVIEWING: TURNING INTERROGATIONS INTO CONVERSATIONS - Grossman, Stephen (NBP. Nauka, bezbednost, policija, 2017)
Abstract: An interrogation is essentially combative and high pressure, and therefore most often a negatively charged monologue of an interrogator trying to work a confession out of a subject. In the following, there should be removed from any ethical, effective investigative interviewing practice: interrogation, combative, pressure, monologue and confession. Effective, ethical investigative interviews should be conversational, non-combative and should not seek confessions as a primary objective. Pressuring subjects (including suspects, witnesses or victims) forces people to lie, go silent or to become uncooperative. Pressure and accusations trigger defensive responses. They also cause panic and fear which impacts a person’s cognitive ability to remember and even to communicate. How often people in shock are left stuttering or unable to form coherent sentences or to remember a question asked seconds earlier? Combine the intimidation of being questioned by police, the fear of going to jail and the humiliation of being judged badly by people in authority or by one’s family and friends, as well as fear of reprisals for informing on other criminals, and one easily ends up with “no comment” interviews or flat out lies. Forcing subjects to admit a version of events in order to overcome “no comment” responses or flat out lies leads to poor conviction rates and wrongful convictions. The alternative, which has proven highly effective when practiced within a well-defined, controlled process, is a managed conversation that relaxes a subject and provides an environment and communication framework that inspires an exchange.